2000
DOI: 10.1002/1097-0223(200008)20:8<648::aid-pd869>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fetal sex in screening for Down syndrome in the second trimester using AFP and free ?-hCG

Abstract: In a study of 30 802 unaffected pregnancies and 90 cases of Down syndrome I have analysed second trimester maternal serum alpha‐fetoprotein (AFP) and free β‐human chorionic gonadotrophin (β‐hCG) and grouped the data by fetal sex. In pregnancies with an unaffected female fetus maternal serum AFP was significantly lower (3%) than in the presence of a male fetus, whilst free β‐hCG was significantly raised (7%) in the presence of a female fetus. These differences led to a significantly higher false positive rate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 26 publications
3
14
1
Order By: Relevance
“…Furthermore hCG promotes angiogenesis in the uterine vasculature and blocks any immunological action by the mother on foreign invading placental cells . Previous studies show that women carrying a female fetus have higher serum levels of hCG compared with women carrying a male fetus . In our own birth cohort the same phenomenon was observed (data not shown).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore hCG promotes angiogenesis in the uterine vasculature and blocks any immunological action by the mother on foreign invading placental cells . Previous studies show that women carrying a female fetus have higher serum levels of hCG compared with women carrying a male fetus . In our own birth cohort the same phenomenon was observed (data not shown).…”
Section: Discussionsupporting
confidence: 82%
“…Only recently, however, it has been demonstrated that these gender-associated differences exist at an even earlier stage of the pregnancy. Spencer et al [3] observed, in euploid pregnancies with a female foetus, higher levels of free b-hCG and lower levels of alphafetoprotein (AFP) in the second trimester, thus contributing to higher false positive rates in female foetuses relative to male when screening for aneuploidies.…”
Section: Screening For Chromosome Abnormalities First Trimester Of Prsupporting
confidence: 79%
“…The absence of an effect of child sex on first trimester AFP has been reported also by others [30, 45]. It should be noted, however, that most studies show differences during the second trimester, with mothers of girls having lower concentrations than mothers of boys [46, 47]. No differences in maternal IGF-I by fetal sex have been reported previously [48], despite that cord blood IGF-I has been found to be higher in girls than in boys [4951].…”
Section: Discussionmentioning
confidence: 64%